Oscillatoria sp. as a Potent Anti-phytopathogenic Agent and Plant Immune Stimulator Against Root-Knot Nematode of Soybean cv. Giza 111 - Ghareeb, Rehab Y.; Abdelsalam, Nader R.; El Maghraby, Dahlia M.; Ghozlan, Mahmoud H.; EL-Argawy, Eman; Abou-Shanab, Reda A. I. (Frontiers in Plant Science, 2022)
Background Plant-parasitic nematodes are one of the major constraints to soybean production around the world. Plant-parasitic nematodes cause an estimated $78 billion in annual crop losses worldwide, with a 10–15% crop yield loss on average. Consequently, finding and applying sustainable methods to control diseases associated with soybean is currently in serious need. Methods In this study, we isolated, purified, characterized, and identified a novel cyanobacterial strain Oscillatoria sp. (blue-green alga). Based on its microscopic examination and 16S rRNA gene sequence, the aqueous and methanolic extracts of Oscillatoria were used to test their nematicidal activity against Meloidogyne incognita hatchability of eggs after 72 h of exposure time and juvenile mortality percentage in vitro after 24, 48, and 72 h of exposure time and reduction percentage of galls, eggmass, female number/root, and juveniles/250 soil. Also, the efficacy of the extract on improving the plant growth parameter and chlorophyll content under greenhouse conditions on soybean plant cv. Giza 111 was tested. Finally, the expression of PR-1, PR-2, PR-5, and PR15 (encoding enzymes) genes contributing to plant defense in the case of M. incognita invasion was studied and treated with Oscillatoria extract. Results The aqueous and methanolic extracts of Oscillatoria sp. had nematicidal activity against M. incognita. The percentage of mortality and egg hatching of M. incognita were significantly increased with the increase of time exposure to Oscillatoria extract 96.7, 97, and 98 larvae mortality % with S concentration after 24, 48, and 72 h of exposure time. The aqueous extract significantly increased the percentage of Root-Knot nematodes (RKN) of egg hatching, compared with Oxamyl and methanol extract at 96.7 and 97% after 72 h and 1 week, respectively. With the same concentration in the laboratory experiment. Furthermore, water extracts significantly reduced the number of galls in soybean root, egg masses, and female/root by 84.1, 87.5, and 92.2%, respectively, as well as the percentage of J2s/250 g soil by 93.7%. Root, shoot lengths, dry weight, number of pods/plant, and chlorophyll content of soybean treated with Oscillatoria water extract were significantly higher than the control increasing by 70.3, 94.1, 95.5, and 2.02%, respectively. The plant defense system's gene expression was tracked using four important pathogenesis-related genes, PR-1, PR-2, PR-5, and PR15, which encode enzymes involved in plant defense. Conclusions Oscillatoria extract is a potential nematicide against root-knot nematode invasion in soybean.